SINTESIS DAN KARAKTERISASI SENYAWA BaSrA14OR, BaSrA13FeOK dan BaSrAl2Fe2OR - Ismail, Darwin
ABSTRACK: BaSrAl4O8 , BaSrA1 3FeO8 and BaSrAl2Fe2O8 oxides have been synthesized and their crystal structures were determined by XRD diffraction. Their diffraction patterns were very close to that of BaSrGa4O8 , which has space group P6 3 (No. 173). Those compounds have similar structure, with showing A1O4 tetrahedra (as GaO4 ), form the six-membered rings with sharing corners, and the Ba and Sr atoms lie at the large cavities of the six-member rings. Fe atom possibly replace Al atom in the structure. From Proszki analysis in a hexagonal crystal system and P63 space group ( No.173 ), the obtained cell parameters value of a and c of BaSrA1 4O8 , BaSrAl3FeO8 and BaSrAl2Fe2O8 were successively as follows (8.984(2), 8.625(3))A; (10.377 (4), 8.619(5))A, and (10.454(3), 9.140(3))A. From examination of ferroelectric properties with RT-66A oscilloscope instrument, BaSrA13FeO8 compound exhibited a significant hysteresis loop pattern, whereas BaSrA14O8 and BaSrAl2Fe2O8 did not. At applied voltage of 7 V at capacitor to 0.05 F and desk area of 1.54 cm2, BaSrAl3FeO8 compound have Ps ( saturation polarization) is 16.2ÂµCcm2 and polarization remanent Pr(+) and Pr(-) is 4.7 ÂµCcm-2